Jehovah´S Witnesses and Blood Transfusion: Current ethical implications (Research, Society and Development, 2025)
Introduction: Ethical and bioethical issues are addressed when discussing the refusal of Jehovah’s Witnesses (JWs) to accept blood transfusions. The debate involves fundamental principles such as autonomy and beneficence. The article aimed to evaluate the positive and negative aspects related to medical decision-making in transfusing blood to Jehovah's Witness patients in cases of imminent risk of death. Methods: Integrative review is based on scientific articles from the Lilacs, Pubmed, and Scielo databases all with free access. Academic books, legal regulations, and relevant court decisions were also analyzed. Results: According to the Code of Medical Ethics, physicians are prohibited from proceeding with treatment without obtaining informed consent from the patient or a legal representative, except in cases where there is an imminent risk of death. The physician must still perform alternative treatments that are authorized by the patient to avoid death, not directly resorting to non-consensual intervention. Discussion: The refusal to transfuse blood is rooted in the religious beliefs of the JWs, as they consider it a violation of divine commandments. The physician should respect the informed decision of the patient but should consider the implications of this choice on the individual’s life. Recently this issue was discussed by the Superior Federal Court (STF), which decided in favor of religious freedom. Conclusion: Faced with this dilemma, it is essential to expand the available therapeutic arsenal and strengthen the dialogue of doctors with Jehovah’s Witness patients, ensuring that their beliefs are respected without compromising the quality of care received.